ADR ON DISPUTE BETWEEN A CLIENT AND TRADING MEMBER AT THE LEADING STOCK EXCHANGE IN INDIA: A CASE STUDY - Bezawada, Brahmaiah (Indian Journal of Finance and Banking, 2022)
This case is an appeal matter with the Leading Stock Exchange of India Ltd (LSE) with regard to a dispute between a client and a trading member of the LSE. The Appellant contended that the award passed by the arbitrator had not taken into account the evidence, documents and rules of stock exchange properly while determining the case matter and passed the award. Appellant challenged the Award on the grounds that the award was beyond the scope of submissions to the arbitration, non-application of mind, and ignorance of established judicial principles. The Appellate Member has to determine whether there had been any lapses on the part of the arbitration in applying the trading rules and procedures of the Exchange while analyzing the matter, determining the case and passing the award. Based on that, the Appellant Arbitral Tribunal had to decide whether to set aside the award passed by the sole arbitrator, modify the award or uphold it. The findings and conclusions provide inputs for the development of an appropriate regulatory framework for the Futures Market. However, the results may be generalized only in the emerging markets environment. Hence, researchers are suggested to study margin guidelines of futures market, appreciate the dynamics of futures market and apply the same in their future research in India and abroad. JEL Classification Codes: J52, G14.